OK Computer: A Sign of the Political and Ideological Times? - Jeremy Tranmer (Revue LISA)
Most references to music and politics in the 1990s focus on the role of Britpop in Labour’s 1997 landslide victory. This is hardly surprising since members of Blur and Oasis engaged in public displays of support for Tony Blair’s party. Radiohead refused to do so, and songs such as “Electioneering” expressed disillusionment with party politics in general. The dark political themes developed on OK Computer therefore seemed at odds with the celebratory atmosphere of the period in which the album was released. It will be argued that this is in many ways a rather superficial vision, which reflects a tendency to adopt a limited definition of politics and to concentrate solely on parliamentary phenomena. In that respect, Radiohead and OK Computer can, on the contrary, be seen as reflecting (and even shaping) political changes that were taking place among young people.